Working Holidays for Overseas Doctors: Host Perspective in Mission Hospitals in Rural India - Jesudian Gnanaraj (Health for All Nations, 2015)
Many doctors are willing to spend part of their holidays helping mission hospitals. Some are senior physicians who can contribute a great deal to the program. We describe how it was possible to use their time effectively. We also describe some of the difficulties encountered and the benefits that were obtained from their efforts.Junior doctors helped mission hospitals in many ways, doing a variety of studies and preparing the protocols for the hospital to use. Senior doctors introduced procedures like vaporization surgery and Lift laparoscopic surgery that benefitted rural patients greatly. They also taught new procedures and helped with the publication of research findings. The visitors benefitted as well, a win-win situation.